Serum Matrix Metalloproteinase‐9 and Cognitive Impairment After Acute Ischemic Stroke. Issue 1 (6th January 2018) - Zhong, Chongke; Bu, Xiaoqing; Xu, Tan; Guo, Libing; Wang, Xuemei; Zhang, Jintao; Cui, Yong; Li, Dong; Zhang, Jianhui; Ju, Zhong; Chen, Chung‐Shiuan; Chen, Jing; et al.
Abstract : Background: The impact of serum matrix metalloproteinases‐9 (MMP‐9) on cognitive impairment after ischemic stroke is unclear. We aimed to investigate the association between serum MMP‐9 in the short‐term acute phase of ischemic stroke and cognitive impairment at 3 months. Methods and Results: Our study was based on a subsample from the CATIS (China Antihypertensive Trial in Acute Ischemic Stroke); a total of 558 patients with serum MMP‐9 levels from 7 of 26 participating sites of the trial were included in this analysis. Cognitive impairment severity was categorized as severe, mild, or none (Mini‐Mental State Examination score, <23, 23–26, or ≥27, respectively; Montreal Cognitive Assessment score, <20, 20–24, or ≥25, respectively). Cognitive impairment was defined as a score of <27 for Mini‐Mental State Examination or <25 for Montreal Cognitive Assessment. According to Mini‐Mental State Examination score, 143 participants (25.6%) had mild cognitive impairment and 153 (27.4%) had severe cognitive impairment at 3 months. After adjustment for age, National Institutes of Health stroke score, education, and other covariates, the odds ratio for the highest quartile of serum MMP‐9 compared with the lowest quartile was 3.20 (95% confidence interval, 1.87–5.49) for cognitive impairment. Multiple‐adjusted spline regression model showed a linear association between MMP‐9 levels and cognitive impairment ( P <0.001 for linearity). Sensitivity and subgroup analyses further confirmed these results. Similar significant findings were observed when cognitive impairment was defined by Montreal Cognitive Assessment score. Conclusions: Increased serum MMP‐9 levels in the short‐term phase of ischemic stroke were associated with 3‐month cognitive impairment, independently of established risk factors.